Spatiotemporal distribution and pollution assessment of trace metals in the Buriganga River, Bangladesh - Md. Khadimull Bashar; Kazushi Noro; Qi Wang; Masahiro Tokumura; Ikuko Mori; Mohammad Raknuzzaman; Anwar Hossain; Takashi Amagai (IWA Publishing, 2023)
The Buriganga River plays a key role in the socioeconomic structure of Dhaka, the capital of Bangladesh. However, this river is severely polluted and is considered one of the most polluted in the world. Therefore, this study aimed to assess the concentrations of various metals in the Buriganga River. A study was conducted from August 2019 to February 2020 to determine the concentrations of 16 metals in water samples (n = 210) collected from 10 distinct sites in the Buriganga River. The mean values for the concentrations of Cr, Mn, Ni, Zn, As, Se, Cd, Sb, and Pb in river water were above the guideline values prescribed by the WHO, Japan, and Bangladesh. Moreover, the fraction ratios of Be, Cr, Co, Ni, Cu, Zn, Se, Mo, Ag, Cd, Sb, and Pb were high (>0.85); consequently, these metals could accumulate at high concentrations in river sediments. Assessment using the single-factor pollution index allowed the classification of the pollution level as 'serious pollution' for Sb and 'heavy pollution' for Cd, Ni, and Pb. The trace metal concentrations in this river imply that crops cultivated along the river using river water may also be contaminated with trace metals. HIGHLIGHTS The highest concentrations of Cr, Mn, Co, Ni, Zn, As, Se, Mo, Cd, Sb, and Pb were above the guideline values.; High fraction ratio values of Be, Cr, Co, Ni, Cu, Zn, Se, Mo, Ag, Cd, Sb, and Pb indicated that these metals were distributed on suspended solids.; A single-factor pollution index showed that the Buriganga River was heavily polluted by Sb, Cd, Ni, and Pb.; Mn showed relatively high concentrations in the dry season.;